2022
DOI: 10.3889/oamjms.2022.9237
|View full text |Cite
|
Sign up to set email alerts
|

Servant Leadership and Job Satisfaction and Organizational Commitment: Empirical Evidence from Surabaya Health Care Sector

Abstract: Background: The concept of Servant Leadership has grown as a distinct management style with numerous applications in management research since its inception. It is likely one of the most successful styles for earnest management and for having a good attitude and concern for those around social organizations' well-being and quality of life. Quality human resources are essential to high commitment and satisfaction at work. Satisfy human resources who are committed will take care of the interests of the organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 98 publications
0
1
0
Order By: Relevance
“…Servant leadership and compensation support the creation of nurses' commitment to the organization, this is in line with previous research which concluded that the nature of leaders with servant leadership patterns seeks to serve the needs of their members (Uktutias et al, 2022), so that these leadership behaviors create dynamic conditions in which employees remain loyal to help the organization achieve its goals (Howladar & Rahman, 2021). The nurse's commitment to the organization shows her partiality to remain faithful to stay in the organization and help achieve its goals, this is realized because the leadership that is applied seeks to provide special attention to meet and serve the needs of nurses to carry out their role as executors of nursing duties, the services provided can be in the form of assistance seeks to direct nurses to be able to carry out nursing services optimally for patients, and also provide career support as a reward for work performance which will make nurse loyalty continue to increase while remaining in the organization to help achieve organizational goals.…”
Section: The Effect Of Servant Leadership and Compensation On Organiz...supporting
confidence: 87%
See 3 more Smart Citations
“…Servant leadership and compensation support the creation of nurses' commitment to the organization, this is in line with previous research which concluded that the nature of leaders with servant leadership patterns seeks to serve the needs of their members (Uktutias et al, 2022), so that these leadership behaviors create dynamic conditions in which employees remain loyal to help the organization achieve its goals (Howladar & Rahman, 2021). The nurse's commitment to the organization shows her partiality to remain faithful to stay in the organization and help achieve its goals, this is realized because the leadership that is applied seeks to provide special attention to meet and serve the needs of nurses to carry out their role as executors of nursing duties, the services provided can be in the form of assistance seeks to direct nurses to be able to carry out nursing services optimally for patients, and also provide career support as a reward for work performance which will make nurse loyalty continue to increase while remaining in the organization to help achieve organizational goals.…”
Section: The Effect Of Servant Leadership and Compensation On Organiz...supporting
confidence: 87%
“…Organizational citizenship behavior is created through the commitment of its members to the organization (Indriati et al, 2017;Planer, 2019) because organizational commitment is the strongest effect, where people identify with requests and are highly motivated to carry them out, even when the source of motivation is no longer present (McShane & Glinow, 2015) and organizational commitment is one of the elements used in evaluating employees which includes loyalty to their work, position and organization, and an employee's loyalty is reflected in the three pillars namely affective, sustainability and normative commitment (Allen & Meyer, 2013). Employee commitment is certainly formed through several factors, one of which is leadership style (Latt, 2019) and servant leadership is a form of leadership capable of increasing employee commitment to the organization (Howladar & Rahman, 2021;Uktutias et al, 2022) because individuals with servant leadership style are service-oriented to their members, rather than prioritizing their ambitions, and seek to build solid cooperation between leaders and members for the achievement of organizational goals (Greenleaf, 2015). In addition, commitment to the organization can be built through a form of work motivation (Erdurmazlı, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Servant leadership can successfully foster employee commitment, 70 , 88 , 89 job embeddedness, 52 servant motivation, 40 psychological well-being, 50 voice behavior, 69 person-organization fit, 70 proactive behavior, 48 and satisfaction at work. 70 , 86 , 87 , 90 Furthermore, servant leadership is positively associated with innovative behavior, 71 job performance, 53 , 71 , 86 and pro-environmental behavior.…”
Section: Resultsmentioning
confidence: 99%